Conjugated Main Chain Azo‐Polymers Based on Polycyclic Aromatic Hydrocarbons. Issue 22 (7th October 2019) - Wiktorowicz, Szymon; Damlin, Pia; Salomäki, Mikko; Kvarnström, Carita; Tenhu, Heikki; Aseyev, Vladimir
Abstract: A reductive coupling reaction employing sodium bis(2‐methoxyethoxy) aluminum hydride is used to prepare main chain azo‐polymers comprising of polycyclic aromatic hydrocarbons (naphthalene, anthraquinone, or fluorenone) from their dinitro‐derivatives. The azo‐bridges act as effective means of conjugation and all polymers exhibit differences in the ultra‐violet–visible light absorption and photoluminescence emission spectra depending on the degree of polymerization. Furthermore, in the case of poly(azofluorenone)s and poly(azoanthraquinone)s, these spectra may be modified by changes in the protonation state of the polymers. The lowest unoccupied molecular orbital and highest occupied molecular orbital energy levels and the band gap of poly(azoanthraquinone) are estimated from cyclic voltammetry data and UV–visible absorption of films. Abstract : Main chain azo‐polymers comprising of polycyclic aromatic hydrocarbons (naphthalene, anthraquinone, or fluorenone) are synthesized from corresponding dinitro‐derivatives as repeating units. The azo‐bridges act as effective means of conjugation. These n‐type semiconductor materials may find use as counterparts for the available p‐type materials and be utilized in further development of new organic electronics.